ANALISIS KEMAMPUAN SISWA MENYELESAIKAN SOAL MATEMATIKA BERBASIS HOTS (HIGHER ORDER THINKING SKILLS) PADA MATERI PEMBAGIAN DI KELAS IV DI SDN 104218 SIDOMULYO - Muhammidah, Annisa; Sutarini, Sutarini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The objective of this research was to determine students' ability to solve HOTS-based mathematics problems on the division material in grade IV at SDN 104218 Sidomulyo, to identify students' responses to the given instrument, as well as to examine the validity, reliability, and discriminatory power of the HOTS-based mathematics problem instrument on the division material in grade IV at SDN 104218 Sidomulyo, consisting of 10 questions. This research was a quantitative study using a descriptive method. The population in this research consisted of 43 students, while the sample included 24 students. The research instrument comprised 10 HOTS-based mathematics problems on the division material for grade IV and 20 questionnaire statements on student responses. Data analysis was conducted using SPSS software. The results of this research showed that students' abilities were classified as Very High for 2 students (8.3%), High for 3 students (12.5%), Moderate for 11 students (45.8%), Low for 3 students (12.5%), and Very Low for 5 students (20.8%). Students' absorption rate was 60.7%. The majority of the sample gave a positive response to the problem instrument. Out of the 10 instrument items, all were deemed valid and reliable, with 3 questions having good discriminatory power and 7 questions having very good discriminatory power.